Structure-Based Design of Irreversible Human KAT II Inhibitors: Discovery of New Potency-Enhancing Interactions - Tuttle, Jamison B; Anderson, Marie; Bechle, Bruce M; Campbell, Brian M; Chang, Cheng; Dounay, Amy B; Evrard, Edelweiss; Fonseca, Kari R; Gan, Xinmin; Ghosh, Somraj; Horner, Weldon; James, Larry C; et al. (ACS medicinal chemistry letters, 2013)
A series of aryl hydroxamates recently have been disclosed as irreversible inhibitors of kynurenine amino transferase II (KAT II), an enzyme that may play a role in schizophrenia and other psychiatric and neurological disorders. The utilization of structure–activity relationships (SAR) in conjunction with X-ray crystallography led to the discovery of hydroxamate 4, a disubstituted analogue that has a significant potency enhancement due to a novel interaction with KAT II. The use of k inact/K i to assess potency was critical for understanding the SAR in this series and for identifying compounds with improved pharmacodynamic profiles.